From weed to cash crop: Amaranth - WRENmedia (Technical Centre for Agricultural and Rural Cooperation, 2008)
Amaranth is widely regarded as an unwanted and stubborn weed, food for the poor during hungry periods. It is, however, a highly nutritious and tasty plant. Recently, the Kenya Seed Company has released an improved variety of amaranth which matures in just 2-3 months, has a long harvesting period and produces nutrient-packed grain as well as leaves. In western Kenya, the plant is now being deliberately intercropped with soybean, a practice which both increases fresh leaf yields and improves the quality of the soil.